Decitabine and vorinostat with FLAG chemotherapy in pediatric relapsed/refractory AML: Report from the therapeutic advances in childhood leukemia and lymphoma (TACL) consortium. Issue 5 (8th March 2022) - Pommert, Lauren; Schafer, Eric S.; Malvar, Jemily; Gossai, Nathan; Florendo, Ellynore; Pulakanti, Kirthi; Heimbruch, Katelyn; Stelloh, Cary; Chi, Yueh‐Yun; Sposto, Richard; Rao, Sridhar; Huynh, Van Thu; et al.
Abstract: Survival outcomes for relapsed/refractory pediatric acute myeloid leukemia (R/R AML) remain dismal. Epigenetic changes can result in gene expression alterations which are thought to contribute to both leukemogenesis and chemotherapy resistance. We report results from a phase I trial with a dose expansion cohort investigating decitabine and vorinostat in combination with fludarabine, cytarabine, and G‐CSF (FLAG) in pediatric patients with R/R AML [NCT02412475]. Thirty‐seven patients enrolled with a median age at enrollment of 8.4 (range, 1–20) years. There were no dose limiting toxicities among the enrolled patients, including two patients with Down syndrome. The recommended phase 2 dose of decitabine in combination with vorinostat and FLAG was 10 mg/m 2 . The expanded cohort design allowed for an efficacy evaluation and the overall response rate among 35 evaluable patients was 54% (16 complete response (CR) and 3 complete response with incomplete hematologic recovery (CRi)). Ninety percent of responders achieved minimal residual disease (MRD) negativity (<0.1%) by centralized flow cytometry and 84% (n = 16) successfully proceeded to hematopoietic stem cell transplant. Two‐year overall survival was 75.6% [95%CI: 47.3%, 90.1%] for MRD‐negative patients vs. 17.9% [95%CI: 4.4%, 38.8%] for those with residual disease ( p  < .001). Twelve subjects (34%) had known epigenetic alterations with 8 (67%) achieving a CR, 7 (88%) of whom were MRD negative. Correlative pharmacodynamics demonstrated the biologic activity of decitabine and vorinostat and identified specific gene enrichment signatures in nonresponding patients. Overall, this therapy was well‐tolerated, biologically active, and effective in pediatric patients with R/R AML, particularly those with epigenetic alterations.